2015
DOI: 10.5489/cuaj.3113
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morbidity of ablative energy-based salvage treatments for radio-recurrent prostate cancer

Abstract: Introduction:We compared the morbidity of whole gland salvage ablation using cryotherapy (CRYO) and high-intensity focused ultrasound (HIFU) for radio recurrent prostate cancer at a single centre over a 17-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In the remaining 18 studies, more than one primary modality was used, and 15 studies of which reported the percentage of each modality. Of those 15, only nine studies reported that more than 70% of patients received primary EBRT [ 26 , 29 , 33 , 38 , 40 , 41 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Across all studies, ADT was initiated as adjuvant therapy in four studies [ 28 , 42 , 54 , 56 ], neoadjuvant therapy in seven studies [ 30 , 33 , 36 , 37 , 41 , 44 , 50 ], and both adjuvant and neoadjuvant in two studies [ 29 , 40 ].…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…In the remaining 18 studies, more than one primary modality was used, and 15 studies of which reported the percentage of each modality. Of those 15, only nine studies reported that more than 70% of patients received primary EBRT [ 26 , 29 , 33 , 38 , 40 , 41 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Across all studies, ADT was initiated as adjuvant therapy in four studies [ 28 , 42 , 54 , 56 ], neoadjuvant therapy in seven studies [ 30 , 33 , 36 , 37 , 41 , 44 , 50 ], and both adjuvant and neoadjuvant in two studies [ 29 , 40 ].…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Of those 15, only nine studies reported that more than 70% of patients received primary EBRT [ 26 , 29 , 33 , 38 , 40 , 41 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Across all studies, ADT was initiated as adjuvant therapy in four studies [ 28 , 42 , 54 , 56 ], neoadjuvant therapy in seven studies [ 30 , 33 , 36 , 37 , 41 , 44 , 50 ], and both adjuvant and neoadjuvant in two studies [ 29 , 40 ]. Nineteen studies reported on ADT with no further details [ 26 , 31 , 32 , 34 , 35 , 39 , 43 , 45 , 46 , 48 , 49 , 51 , 52 , 53 , 55 , 57 , 58 , 59 ], and three studies did not report on the use of ADT [ 27 , 38…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…1 Likewise the incontinence rate following salvage HIFU reported is at the low end of current reports. The more serious complications of "need for surgical intervention" or fistula formation are in the expected range.…”
mentioning
confidence: 73%
“…Chin and his group are to be commended for their ongoing assessment of salvage therapies in selected patients with recurrent prostate cancer post-radiation therapy. 1 Over many years, the authors have scientifically evaluated cryosurgery and high-intensity focused ultrasound (HIFU). Earlier publications have helped to delineate the selection criteria of those cases most likely to succeed.…”
mentioning
confidence: 99%